FENOMENA OVER EDUCATION DAN UNDER EDUCATION DALAM PASAR KERJA WANITA - Wiko Saputra; Junaidi Junaidi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
The phenomenon of over education and under education is a phenomenon in which a labor force with higher education levels hold jobs that do not fit with the level of education. The opposite, someone with a lower educational level would occupy a higher job. This study uses data SUSENAS 2009 for the Province of West Sumatra. The research shows, there is the phenomenon of over education and under education in the female labor market in West Sumatra and there are significant income related to the phenomenon of over education and under education in the women of labor market. It is necessary to link and match between education and female labor market in the formal sector. The policy of labor exploitation through unfair wage system for workers needs to be done so that the phenomenon of over education and under education will have positive impact for companies and workers concerned.